الحماية من مخاطر استثمار الأوقاف: دراسة تأصيلية - المحيميد، عمر بن إبراهيم بن محمد (جامعة القصيم, 2021)
Research Topic: Discussing the rules related to protecting endowments’ investment from risks and the provisions controlling legitimate protection of endowments’ investment. Research Objectives: To examine the ruling on providing protection from risks for endowments investment and to identify the regulations related to legitimate protection of endowments’ investment. Research Methodology: the blended methodology of inductive, analytical, and deductive approaches. Summary and the Most Important Results: Islamic scholars gave different rulings regarding the issue of investing endowment funds. There are two main rulings; one of them forbids investing endowment funds; while the other permits investing endowment funds but in certain cases. However, I mentioned in the study the most correct ruling, which is the one that is permits investing endowment funds- along with its controls. Therefore, I stated various areas of investment briefly. After thorough research and study, I managed to collect the most important provisions and regulations related to investing endowments. It also became clear to me that the ruling on protecting endowments’ investments from risks differs according to investment’s type. Some scholars ruled that it is prohibited to protect endowments’ investments from risks. While some other ruled that it is permitted to do so. Nonetheless, the scholars who permitted protecting endowments’ investments from risks, did not agree upon the degree of that action as some of them said that it is ‘preferable’ (Arabic: Mandoub), whereas some stated that it is ‘permissible’ (Arabic: Mubah). However, they agreed that the degree of this action depends upon the type of protection and the nature of the risk. The study discussed as well the controls of the obligatory protection and the permissible protection. Furthermore, the most famous applications of obligatory protection have been mentioned. The most important recommendations: I recommended conducting further research and focusing on modern fiqh issues, including those related to endowments and the newly emerging issues with relation to endowments- especially the issue of means of protection which emerges every now and then- in order to examine and identify the rulings related to them.
موضوع البحث: الحماية من مخاطر استثمار الأوقاف- دراسة تأصيلية، وضوابط الحماية المشروعة لاستثمار الأوقاف. -أهداف البحث: بيان حكم الحماية من مخاطر استثمار الأوقاف، وبيان ضوابط الحماية المشروعة لاستثمار الأوقاف. -منهج البحث: المنهج الاستقرائي التحليلي الاستنباطي. -الملخص وأهم النتائج: اختلف الفقهاء في حكم استثمار أموال الأوقاف على قولين بين مانع ومجيز، ومجيز في حالات معينة، وقد ذكرت أن القول الراجح هو القائل بالجواز- بضوابطه، وذكرت مجالات الاستثمار- مختصرا-، وبعد البحث والتقصي جمعت أهم ضوابط استثمار الأوقاف، كما تبين لي أن حكم الحماية من مخاطر استثمار الأوقاف يختلف باختلاف ماهيتها، فيدور الحكم بين المشروعية وبين عدمها، والمشروع منها ينقسم إلى: الوجوب، وعدمه- أي: الندب أو الإباحة؛ وذلك راجع لنوع الحماية ولجنس الخطر ومداه، كما تبين لي ضوابط الحماية الواجبة والحماية المشروعة، وقد تم ذكر أشهر تطبيقات الحماية المشروعة مع بيان مختصرا لها. -أهم التوصيات: أوصي بالتركيز على بحث المسائل الفقهية المتجددة ومنها المتعلقة بالأوقاف وما يستجد فيها، خاصة دراسة وسائل الحماية والتي تتجدد في كل حين وتتطور، وإصدار الأحكام المتعلقة بها.
Keywords: الوقف الإسلامي -- الأوقاف الإسلامية -- الاستثمار الوقفي -- المخاطر الاستثمارية -- الشريعة الإسلامية